2014
DOI: 10.1016/j.celrep.2014.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Uptake and Lipid Storage Induced by HIF-1α Contribute to Cell Growth and Survival after Hypoxia-Reoxygenation

Abstract: An in vivo model of antiangiogenic therapy allowed us to identify genes upregulated by bevacizumab treatment, including Fatty Acid Binding Protein 3 (FABP3) and FABP7, both of which are involved in fatty acid uptake. In vitro, both were induced by hypoxia in a hypoxia-inducible factor-1α (HIF-1α)-dependent manner. There was a significant lipid droplet (LD) accumulation in hypoxia that was time and O2 concentration dependent. Knockdown of endogenous expression of FABP3, FABP7, or Adipophilin (an essential LD st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
494
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(531 citation statements)
references
References 62 publications
32
494
1
4
Order By: Relevance
“…It has been also reported that tendon retraction in full‐thickness medium‐sized RCT is characterized by neovascularity, increased VEGF/HIF expression, fatty infiltration, and muscle atrophy,40 showing substantial involvement of HIF1 in RCT. In addition, a recent study demonstrated that FABP3 and FABP7 are induced by HIF‐1α and lead to a significant lipid droplet accumulation in hypoxia 47. Together with our present finding, these evidences indicate that RCT‐induced hypoxic condition activates HIF1 and further regulates FABP expression ( Figure 6).…”
Section: Discussionsupporting
confidence: 89%
“…It has been also reported that tendon retraction in full‐thickness medium‐sized RCT is characterized by neovascularity, increased VEGF/HIF expression, fatty infiltration, and muscle atrophy,40 showing substantial involvement of HIF1 in RCT. In addition, a recent study demonstrated that FABP3 and FABP7 are induced by HIF‐1α and lead to a significant lipid droplet accumulation in hypoxia 47. Together with our present finding, these evidences indicate that RCT‐induced hypoxic condition activates HIF1 and further regulates FABP expression ( Figure 6).…”
Section: Discussionsupporting
confidence: 89%
“…Cancer is associated with dysregulated lipid metabolism both at the systemic and paracrine level and intracellular lipid accumulation may promote cancer cell aggressiveness (6,(36)(37)(38). Most studies involve the role of de novo lipogenesis from increased utilization of glucose carbons and autocrine processes, whereas the importance of extracellular lipids of the tumor microenvironment remains relatively ill-defined.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia enhances aggressive tumor attributes but correlates negatively with a decrease in outcome [22]. Fatty acid uptake and lipid storage are enhanced by hypoxia-inducible factor 1 alpha and may contribute to tumor cell growth after hypoxia-reoxygenation [23].…”
Section: Constitutional Attributesmentioning
confidence: 99%